LOGICAL AND CONCEPTUAL CONSTRUCTIONS, THEORETICAL AND LEGAL VERSIONS OF THE INTERPRETATION OF THE ARTIFICIAL INTELLIGENCE’S "LEGAL PERSONALITY" - V. Gaivoronskaya, Yana; Y. Mamychev, Alexey; I. Miroshnichenko, Olga; Khotynska-Nor, Oksana (Revista Gênero e Interdisciplinaridade, 2021)
The lack of sufficient legal regulation of relations associated with the use of artificial intelligence and robotics is associated with the conceptual lack of resolution of the basic issues underlying modern models of legal regulation for anything: about the concept and general status of the phenomenon to be settled. With regard to the research topic, this translates into questions about the concept and legal personality of artificial intelligence. These questions represent a kind of logical metaphor: in order to start modeling the legal personality of artificial intelligence, we must first define its concept; and the legal concept of artificial intelligence will be formulated differently depending on whether we consider it as a subject or an object of law. The authors investigate the technical, moral and legal aspects of the problem concerning the status and understanding artificial intelligence, and draw conclusions about the basic conditions for the legal regulation of this area.